2013
DOI: 10.1074/jbc.m112.446054
|View full text |Cite
|
Sign up to set email alerts
|

Type I Phosphotidylinosotol 4-Phosphate 5-Kinase γ Regulates Osteoclasts in a Bifunctional Manner*

Abstract: Background: PI(4,5)P 2 , mainly synthesized by PIP5KI␥, is essential for normal cell function. Results: Deficiency or overexpression of PIP5KI␥, which results in decrease or increase of PI(4,5)P 2 , respectively, impairs osteoclast differentiation and function. Conclusion: Optimal PIP5KI␥ and PI(4,5)P 2 expression are important for osteoclast function. Significance: This is the first demonstration that PIP5KI␥ regulates cells in a bifunctional manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, PLD1- and PLD2-generated PA is reported to activate and directly regulate PIP5K activity 38,93,94 , and PLD2 can recruit PIP5K to the membrane 95 . Finally, PIP5K has been show to localize at podosome rings in osteoclasts 96 . Since our data show that both PLD1 and PLD2, albeit with some differences, promote podosome formation in a non-redundant concurrent manner (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, PLD1- and PLD2-generated PA is reported to activate and directly regulate PIP5K activity 38,93,94 , and PLD2 can recruit PIP5K to the membrane 95 . Finally, PIP5K has been show to localize at podosome rings in osteoclasts 96 . Since our data show that both PLD1 and PLD2, albeit with some differences, promote podosome formation in a non-redundant concurrent manner (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Type I Phosphotidylinosotol 4-Phosphate 5-Kinase (PIP5KI) has three isoforms, α, β, and γ. The PIP5KI γ highly abundant in brain and plays important role in cytoskeletal organization [42,43]. SAM50 and TOM70, are…”
Section: Discussionmentioning
confidence: 99%
“…Xu and colleagues have reported that the polarization of Pip5k1c induced by integrins is required for the recruitment of neutrophils during inflammatory responses [20]. Zhu et al have reported that excessive Pip5k1c expression impairs osteoclast formation and bone resorption via enhancing the Pip2 generation [24]. Our previous study has demonstrated an essential role of Pip5k1c, through its expression in mesenchymal stem cells (MSCs), in the control of bone remodeling [25].…”
mentioning
confidence: 90%